1996
DOI: 10.1002/j.1460-2075.1996.tb00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Homophilic adhesion of E-cadherin occurs by a co-operative two-step interaction of N-terminal domains.

Abstract: Cluster formation of E‐cadherin on the cell surface is believed to be of major importance for cell‐cell adhesion. To mimic this process the extracellular part of mouse E‐cadherin (ECAD) was recombinantly fused to the assembly domain of rat cartilage oligomeric matrix protein (COMP), resulting in the chimeric protein ECAD‐COMP. The COMP domain formed a five‐stranded alpha‐helical coiled‐coil. This enabled the formation of a pentameric ECAD with bundled C‐termini and free N‐termini. The pentameric protein constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
149
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(168 citation statements)
references
References 32 publications
18
149
0
1
Order By: Relevance
“…2, right). This observation on Ca 2+ -loaded Ecadl2 is consistent with previous crystallographic and electron microscopy studies showing that calcium extends and rigidities the extracellular segment of E-cadherin [7] and that lateral association of adjacent extracellular segments occurs at the N-terminal tip of the molecule [8].…”
Section: Apo Ecad12supporting
confidence: 92%
“…2, right). This observation on Ca 2+ -loaded Ecadl2 is consistent with previous crystallographic and electron microscopy studies showing that calcium extends and rigidities the extracellular segment of E-cadherin [7] and that lateral association of adjacent extracellular segments occurs at the N-terminal tip of the molecule [8].…”
Section: Apo Ecad12supporting
confidence: 92%
“…Interestingly, this is the approximate length of a cadherin extracellular domain if all the repeats would be in a straight line, one after the other. However, as noted earlier, electron microscopy of the extracellular domain of Ecadherin and the crystal structure of the full-length extracellular domain of C-cadherin depict the cadherin extracellular domain as a bent rod (Pokutta et al 1994;Tomschy et al 1996;Ahrens et al 2002;Boggon et al 2002). Due to the curve of the extracellular domain, the trans-adhesion dimer proposed by Boggon et al (2002) would occur between surfaces approximately 25 nm apart.…”
Section: Further Functional Studies Of Ec Domains In Adhesionmentioning
confidence: 75%
“…First, further work on ECADCOMP showed that adhesive pentamers oligomerized through the N-terminal regions of E-cadherin (Tomschy et al 1996;Koch et al 1999;Pertz et al 1999). It is unclear, however, exactly which parts of the N-terminus are involved in adhesion.…”
Section: Further Functional Studies Of Ec Domains In Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the linear dimension of the full-length extracellular domain is 22 Ϯ 1 nm (9,21,22), and the length of the DSIDA linker is ca. 1 nm, the proteins should interdigitate completely at D Ͻ 25 Ϯ 1 nm (9,21,22). We therefore attribute the repulsive force at D Ͻ 25 nm to steric interactions between the proteins and the opposing bilayer surface.…”
Section: Definition Of the Intersurface Separation Distance Dmentioning
confidence: 99%